Acoustic investigation of the carillonsin Poland - SANKIEWICZ, M.; KACZMAREK, A.; BUDZYŃSKI, G. (Archives of Acoustics, 1994)
The carillons existing in Poland are described. Three carillons have been recently investigated acoustically: that as Jasna Góra Sanctuary in Częstochowa, installed in 1905, that one at St. Catherine Church in Gdańsk, built in 1989, and the one at the Gdańsk Main-City town-Hall, rebuilt, yet unsatisfactorily, in 1970. Results of the computerized spectral sound analysis of those carillons are presented, compared and discussed.